Study Experimen Monitoring Laju Gas LPG Menggunakan MQ 6 Sensor Terhadap AFR Pengujian Mesin Genset 160 CC - Nugroho, Berto Yusuf; Finda Yuniarti, Dwi Ariani; Wicaksono, Yoga Arob (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
ABSTRACT Usability of portable generators fueled by petroleum as a substitute for the community's primary source of electrical energy when the main electricity source blackout is still high demand, limited space for good air circulation will make emissions harmful to users or community, innovation is needed to reduce the levels of exhaust emissions produced by saving fuel or converting the fuel used, using monitoring system user could define how the engine working and make a decision to maintaining or modifying the engine, one of which is by replacing the carburetor in portable generators fuel engine with a converter kit using modified Liquified Petroleum Gas (LPG). In this study, the result of Arduino serial monitoring was displayed the lowest use of petroleum fuel was obtained at 36.3 ml/minute (36.300 ppm) at 1000-2000 rpm, consumption of LPG fuel is 5.650 ppm at 1000 rpm, and in the high rpm consumption of LPG is 11.972 ppm, result, the use of LPG fuel in Portable Generators with a converter kit has the effect of using more efficient fuel